Medicinal Plant Used by Indigenous People Namely Suku Anak Dalam (SAD) in Nyogan Village Jambi Province - Upik Yelianti; Muswita Muswita; Dara Mutiara Aswan (Postgraduate, University of Mataram, 2023)
Medicinal plants have long been known and used by the people of Indonesia and are still used today because they rarely cause side effects. One community that still uses plants as traditional medicine is the Suku Anak Dalam (Anak Dalam Tribe) (SAD) which lives in Nyogan Village, Mestong District, Jambi. As a result of the land use change in Jambi, where the forest has shifted to oil palm plantations, the forest as a habitat for medicinal plants is also decreasing, and there is even a concern that there will be a loss of germplasm. This research aimed to find out medicinal plants used by SAD in traditional medicine. This research is qualitative research with in-depth interviews and observation to collect data. The results showed that there were about 17 plants used as traditional medicine by SAD in Nyogan Village. Of the 17 plant species, four plant species were classified rare, namely Mampat wood (Cratoxylum arborescens (Vahl.) Blume), Putat wood (Planchonia valida [B.]), Brumbung wood (Adina minutiflora Val; Pertusadina spp), Bulian wood (Eusideroxylon zwageri L.). The parts of the plant that are often used for traditional medicine are bark, leaves, and plant roots, as internal medicine (oral) and external medicine. The results of this research provide an overview of medicinal plants that are still used by SAD so that they can be preserved in the future